Courses
Courses for Kids
Free study material
Offline Centres
More
Last updated date: 25th Nov 2023
Total views: 278.4k
Views today: 2.78k

# The principal argument of $\dfrac{i-3}{i-1}$ is:$\left( a \right)tan^{-1}\dfrac{1}{2}$$\left( b \right) tan^{-1}\dfrac{3}{2}$$\left( c \right) tan^{-1}\dfrac{5}{2}$$\left( d \right) tan^{-1}\dfrac{7}{2}$

Verified
278.4k+ views
Hint: We are asked to find the principal argument of a given complex number. But we see that it is not in the standard $a+bi$ form. So, we first convert this into the standard form and then apply the definition of principal argument to find the answer. We should be aware of some terms such as argument, principal argument which are related to the imaginary numbers in order to solve this question.

We have $\dfrac{i-3}{i-1}$. We need to first convert this into a standard form. For this, we multiply both numerator and denominator by $i+1$. Doing this we get:
$\dfrac{i-3}{i-1}\times\dfrac{i+1}{i+1}=\dfrac{i^2+i-3i-3}{i^2-1^2}$
We have used the following identity in denominator:
$\left(a+b\right)\left(a-b\right)=a^2-b^2$
We get:
$\dfrac{-1-2i-3}{-1-1}=\dfrac{-4-2i}{-2}=2+i$
Hence, we have found out the complex number in standard form. Now, we know that the principal argument, $Arg\left(z\right)$of any complex number $z=a+bi$is found out using the following formula:
$Arg\left(z\right)=tan^{-1}\left(\dfrac{b}{a}\right)$ if $a>0$
And
$Arg\left(z\right)=tan^{-1}\left(\dfrac{b}{a}\right)+\pi$ if $a<0$
We have $2+i$ as the complex number. So $a=2$ and $b=1$. We conclude that $a>0$, hence the principal argument will be:
$Arg\left(2+i\right)=tan^{-1}\left(\dfrac{1}{2}\right)$

So, the correct answer is “Option a”.

Note: We can also do the same using the following formula:
$Arg\left(\dfrac{z_1}{z_2}\right)=Arg\left(z_1\right)-Arg\left(z_2\right)$
Here, put $z_1=i-3$ and $z_2=i-1$
Then $Arg\left(z_1\right)=tan^{-1}\dfrac{-1}{3}$
And $Arg\left(z_2\right)=tan^{-1}-1$
So, we have:
$Arg \left(\dfrac{i-3}{i-1}\right)= Arg\left(z_1\right)-Arg\left(z_2\right)$
$= tan^{-1}\dfrac{-1}{3}- tan^{-1}-1$
Now, we use the formula below:
$tan^{-1}A- tan^{-1}B=tan^{-1}\left(\dfrac{A-B}{1+AB}\right)$
Using this we obtain the following:
$Arg \left(\dfrac{i-3}{i-1}\right)=tan^{-1}\left(\dfrac{-\dfrac{1}{3}+1}{1+\dfrac{1}{3}}\right)$
$=tan^{-1}\dfrac{1}{2}$
Hence, the answer is obtained correctly. But note that you should use this only when you remember the formula of inverse tan function correctly.